Genetic parameters for milk production traits of Simmental cows with random regression test-day model - A. Otwinowska-Mindur; E. Ptak; W. Jagusiak; A. Zarnecki (Animal)
Precise genetic parameter estimates can allow the breeding value evaluation to be adjusted to meet European requirements and to enable participation in the international evaluation of Simmental bulls conducted by Interbull. Genetic parameters were estimated for a multitrait multilactation random regression test-day model for milk in Simmental cattle in Poland. Data came from the official Polish national recording system. Records of 6 447 Simmental cows born from 2002 through 2021 in 1 046 herds were collected. The cows were daughters of 987 sires and 4 590 dams. A minimum of two daughters per sire was required. Daily yields were collected between 5 and 305 days in milk. The BLUPf90 package and a Bayesian method via Gibbs sampling were used to estimate (co)variance components. The model contained fixed herd-test-date effect, fixed regressions within age-season of calving classes, and random additive genetic and permanent environmental regressions. The Wilmink function was used for fixed regressions, and third-order Legendre polynomials for random regressions. The mean heritability for daily milk yields and milk composition ranged from 0.12 (somatic cell score) to 0.41 (protein content in milk). The majority of the analysed traits were most heritable at the end of 305-d lactation. Genetic correlations between daily milk, fat, protein and lactose yields were positive and high (0.78–0.99). This meant that selection for one of those milk traits indirectly induced a similar response in another milk trait. The lactational heritabilities of all nine traits were much higher than the estimates of average daily heritabilities, and varied from 0.29 for somatic cell score to 0.74 for urea content in milk. For both daily and lactational parameters, traits expressed in percent were more highly heritable than yield traits. The values of the genetic parameters estimated in this paper can be used when a single-trait multilactation random regression test-day animal model for production traits is applied in the official genetic evaluation of the Simmental population, replacing the current lactation model.